Agrarian Reform and Land for Youth?: Responding to Agricultural Gerontocracy among Palm Sugar Farmers in the Menoreh Mountains - Assyifa Khoirunnisa Dewi; Dwi Wulan Pujiriyani; Nur Rahmanto (Sekolah Tinggi Pertanahan Nasional, 2024)
This paper aims to examine the contribution of agrarian reform in addressing the gerontocracy of agriculture in rural areas. The research specifically focuses on examining how the post-agrarian reform program in Gunung Kukusan hamlet has shifted land ownership and control from the older to the younger generation, and how agrarian reform has influenced changes in land management control. The research was conducted using a qualitative approach. Data collection techniques included in-depth interviews, observation, and documentation. Data analysis was carried out qualitatively by categorizing and visualizing the data. The research results clearly demonstrate the issue of agricultural gerontocracy, particularly the tendency to view agricultural activities as a secondary profession. Agrarian reform through asset restructuring and access restructuring does not bring about changes in land control, ownership, and management. Land certification serves as a confirmation of ownership rather than a direct transfer of ownership. The practice of land grabbing shows that management control is entirely in the hands of landowners, most of whom belong to the older generation. The youth lack the authority to make changes to the generations-old coconut farming practices. This situation underscores the need for agrarian reform policies that accommodate the issue of youth landlessness.